O movimento homossexual no Brasil: construção da identidade, eventos e visibilidade mediática - Moraes, Elaine Cristina Gomes de [UNESP]; Soares, Murilo Cesar [UNESP] (USCS Universidade Municipal de Sao Caetano do Sul, 2013)
The lesbian and gay movement has organized itself in Brazil with the goal of creating and making its sexual identity stronger, as well as fighting for its rights and against any homophobic act. This paper analyses the homosexual movement and its relation to building its own identity, as a fighting force. We emphasize the relevance of the manifestation events, such as the LGBT pride parade and, in Bauru, the diversity parade, events that not only provide visibility to the topic, with the presence of the media, but also, represent the voice of these people who search for their citizenship rights.

O movimento homossexual organizou-se no Brasil com o objetivo de criar e fortalecer sua identidade sexual, bem como lutar por seus direitos e contra atos homofóbicos. Este estudo analisa o movimento homossexual e sua relação com a construção de sua identidade, enquanto força de luta. Destaca-se a relevância dos eventos de manifestação, como a Parada do Orgulho LGBT e, em Bauru, a Parada da Diversidade, que proporcionam visibilidade à questão, pela a presença da mídia, e representam a voz desse público que luta por direitos de cidadania.
The lesbian and gay movement in Brazil: construction of identity, events and media visibility
Keywords: Identity; Lesbian and gay movement; Diversity parade in Bauru; Identidade; Movimento homossexual; Parada da diversidade de Bauru